How Profitability, Leverage, Financial Distress, Institutional Ownership, and Capital Intensity affect Accounting Conservatism - Setyanto, Kurniadi; Fitri, Hadiati; Zhafiraah, Nazma Riska (Santoso Academy Network, 2024)
This research seeks to ascertain how accounting conservatism is impacted by institutional ownership, profitability, leverage, financial hardship, and capital incentives. The study employs secondary data, specifically manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2016–2020 timeframe, using a quantitative correlation research approach. Twenty-six companies made up the research sample. Purposive sampling was the method of sampling that was applied. Analysis using multiple linear regression is the analytical technique employed. The study's findings indicate that while financial distress and capital intensity are related to accounting conservatism, profitability, leverage, and institutional ownership do not. Management implications for accounting conservatism in relation to profitability, leverage, financial distress, institutional ownership, and capital are financial strategies. Implications related to capital intensity can influence the company's financial strategy; if capital intensity is related to the level of accounting conservatism, managers can consider a capital structure that is in accordance with conservative goals